2022
DOI: 10.3390/ijms232113237
|View full text |Cite
|
Sign up to set email alerts
|

LMNA Reduced Acquired Resistance to Erlotinib in NSCLC by Reversing the Epithelial–Mesenchymal Transition via the FGFR/MAPK/c-fos Signaling Pathway

Abstract: For patients exhibiting non-small-cell lung cancer (NSCLC) with activating epidermal growth factor receptor (EGFR) mutations, epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are a first-line treatment. However, most patients who initially responded to EGFR-TKIs eventually developed acquired resistance, limiting the effectiveness of therapy. It has long been known that epithelial–mesenchymal transition (EMT) leads to acquired resistance to EGFR-TKIs in NSCLC. However, the mechanisms unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In tumor cells, FGFR inhibits the JAK/STAT signaling pathway activated by T cell‐produced interferon gamma and then reduces the expression of its target genes, namely, beta‐2 microglobulin (B2M), C‐X‐C motif chemokine ligand 10 (CXCL10), and programmed death‐ligand 1 (PD‐L1), thereby mediating immune escape 60 . In non‐small cell lung cancer (NSCLC), FGFR activates the MAPK/c‐Fos pathway to promote tumor cell proliferation, migration, and resistance to erlotinib 61 . Similarly, FGFR promotes cholangiocarcinoma cell progression and resistance to gemcitabine through upregulation of AKT/mammalian target of rapamycin (mTOR) and STAT3 signaling 62 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tumor cells, FGFR inhibits the JAK/STAT signaling pathway activated by T cell‐produced interferon gamma and then reduces the expression of its target genes, namely, beta‐2 microglobulin (B2M), C‐X‐C motif chemokine ligand 10 (CXCL10), and programmed death‐ligand 1 (PD‐L1), thereby mediating immune escape 60 . In non‐small cell lung cancer (NSCLC), FGFR activates the MAPK/c‐Fos pathway to promote tumor cell proliferation, migration, and resistance to erlotinib 61 . Similarly, FGFR promotes cholangiocarcinoma cell progression and resistance to gemcitabine through upregulation of AKT/mammalian target of rapamycin (mTOR) and STAT3 signaling 62 .…”
Section: Introductionmentioning
confidence: 99%
“… 60 In non‐small cell lung cancer (NSCLC), FGFR activates the MAPK/c‐Fos pathway to promote tumor cell proliferation, migration, and resistance to erlotinib. 61 Similarly, FGFR promotes cholangiocarcinoma cell progression and resistance to gemcitabine through upregulation of AKT/mammalian target of rapamycin (mTOR) and STAT3 signaling. 62 The AKT/SRY‐box 2 (SOX2) axis, mediated by FGFR2, also controls the stemness of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the onset of acquired resistance is a common event and dramatically Pace et al Journal of Translational Medicine (2023) 21:626 hampers therapeutic efficacy [63]. FGFR signaling pathways have been described as molecular mechanisms for acquired resistance to TKIs targeting other tyrosine kinase receptors, such as EGFR, c-Met, ALK and CDK4/6 [64][65][66]. Although functional studies are needed, the evidence that pemigatinib treatment can modulate other TKI targets reinforces the biological rationale for combinatorial strategies to overcome TKI resistance and improve clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined resistance to this approach in NSCLC. Hu et al compared NSCLC cells sensitive and resistant to the EGFR inhibitor erlotinib and found that resistant cells exhibited increased Akt activity and an EMT phenotype, including a switch from TWIST2 to TWIST1 expression [115]. The same study found that the expression of LMNA reversed EMT via the inhibition of MAPK signals and preserved drug sensitivity.…”
Section: Emt and Response To Growth Factor Inhibitionmentioning
confidence: 99%